Characteristics of Serum Thyroid Hormones in Different Metabolic Phenotypes of Obesity - Xiaomin Nie; Xiaojing Ma; Yiting Xu; Yun Shen; Yufei Wang; Yuqian Bao (Frontiers in Endocrinology, 2020)
Aim: Metabolically healthy obese (MHO) individuals have attracted broad attention. We aimed to investigate the characteristics of serum thyroid hormones in different metabolic phenotypes of obesity.Methods: The study included 1,023 community-based euthyroid subjects (age range: 27–81 years), of whom 586 were women. Fat% was detected by a bioelectrical impedance analyzer. Two definitions of obesity were applied as follows: (1) fat% ≥ 25% for men and ≥ 30% for women; (2) body mass index (BMI) ≥ 25 kg/m2. According to the diagnostic criteria for metabolic syndrome by the Chinese Diabetes Society, metabolically unhealthy was defined as two or more components of metabolic syndrome, excluding waist circumference. Serum-free triiodothyronine (FT3), free thyroxine (FT4), and thyroid-stimulating hormone (TSH) levels were measured by electrochemiluminescence immunoassay.Results: The proportions of obesity defined by fat% and BMI were 41.3 and 27.1%, respectively. The proportion of metabolically unhealthy was 41.6%. After adjusting for age and gender, regardless of the definitions based on fat% or BMI, FT3 was positively related to both the MHO and the metabolically unhealthy obese (MUO) phenotypes [MHO: odds ratio (OR)s = 1.676 based on fat% and 2.055 based on BMI; MUO: ORs = 1.818 based on fat% and 1.526 based on BMI; all P < 0.05]; FT4 was negatively related to the MUO phenotype (ORs = 0.870 based on fat% and 0.849 based on BMI, all P < 0.05); FT3/FT4 was also positively related to both the MHO and the MUO phenotypes (MHO: ORs = 1.678 based on fat% and 2.825 based on BMI; MUO: ORs = 2.866 based on fat% and 2.883 based on BMI; all P < 0.05); and TSH was positively related to the metabolically unhealthy non-obese phenotype (ORs = 1.329 based on fat% and 1.321 based on BMI, all P < 0.01).Conclusions: In euthyroid population, both the MHO and the MUO phenotypes were characterized by increased FT3 and FT3/FT4 levels.